Severity and management of psoriasis within primary care. Issue 1 (December 2016) - Wade, Alan; Crawford, Gordon; Young, David; Leman, Joyce; Pumford, Neil
Abstract Background Scottish Intercollegiate Guidelines Network and National Institute of Health and Care Excellence guidelines stress the importance of assessing patients with psoriasis for psoriatic arthritis, comorbidities associated with severe disease and quality of life (QoL). The purpose of the study was to evaluate the primary care management of psoriasis in relation to disease severity and QoL from a patient's perspective. Methods A cross-sectional survey of adults (≥18 years) with psoriasis managed in primary care was conducted in Scotland over 1-year (2012–2013). Patients with psoriasis were identified and invited to participate in the online/telephone survey. The questionnaires included; Dermatology Life Quality Index (DLQI), Self-Administered Psoriasis Area and Severity Index (SAPASI), Psoriasis Epidemiology Screening Tool (PEST). The primary outcome measure was DLQI. Secondary outcomes included; demographics; comorbidities; involvement of different body sites; SAPASI and PEST scores. Relationships between measures were analysed using univariate analysis. Results The mean age of patients (n  = 905) was 54.5 years (SD = 16.1), 436 (48.2 %) were men, and median DLQI and SAPASI scores were 4.0 and 6.0, respectively. Current psoriasis treatments were topical only (587, 64.9 %), oral medications or phototherapy (122, 13.5 %), biologics (26, 3 %) and none (156, 17.2 %). Despite SIGN recommendations, 256 of 391 patients (65.5 %) with a DLQI >5 (at least a moderate effect on QoL) had not seen a specialist during the past year. According to PEST scores, 259 patients (28.6 %) had symptoms suggestive of psoriatic arthritis requiring rheumatology referral. Conclusion National recommendations are not being fully implemented in primary care in patients with psoriasis or psoriatic arthritis.